Effects of Thoracic Epidural Anesthesia Combined With Inhalational or Intravenous Anesthesia on Intrapulmonary Shunt During One-Lung Ventilation - Korgün Ökmen; Durdu Kahraman Yıldız; Aycan Kurtarangil Doğan (Indonesian Journal of Anesthesiology and Reanimation, 2026)
Introduction: In thoracic surgery, one-lung ventilation (OLV) may increase intrapulmonary shunt and impair oxygenation, and this effect is modulated by anesthetic technique via its influence on hypoxic pulmonary vasoconstriction. Objective: This study aims to compare whether thoracic epidural anesthesia differentially affects intrapulmonary shunt during one-lung ventilation according to the maintenance anesthetic technique. Methods: This retrospective and observational study included 86 patients who underwent OLV during thoracic surgery. Patients were divided into four groups according to the anesthetic protocol: target-controlled infusion (TCI) (22 patients), TCI combined with thoracic epidural anesthesia (TEA) (21 patients), sevoflurane (22 patients), and sevoflurane combined with TEA (21 patients). The primary outcome was the intrapulmonary shunt (Qs/Qt) ratio, measured at T1 (5 minutes after intubation), T2 (20 minutes after initiation of OLV), and T3 (40 minutes after initiation of OLV) using arterial and venous blood gas analyses. Secondary outcomes included arterial oxygen tension (PaO₂) and hemodynamic parameters measured at T1, T2, and T3. Results: The Qs/Qt ratio was higher in all groups at T2 and T3 measurements than at T1 (p<0.001). A statistically significant difference was found between groups in the Qs/Qt ratio at T2 and T3 measurement times (p<0.05). The shunt ratio was highest in the combination of sevoflurane and TEA group at T2 and T3 times and lowest in the TCI group. No statistically significant difference was found between the groups in PaO2 values at T2 and T3 measurement times. (p>0.05) Conclusion: Inhalation and intravenous anesthesia methods increased shunt volume in thoracic surgery patients undergoing OLV. The addition of thoracic epidural anesthesia was associated with higher estimated shunt fractions in both anesthetic techniques.